Perilaku Siswa Sekolah Dasar dalam Menyelesaikan Soal Cerita Matematika - Yuliandari, Ria Norfika (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Learning word problem can be used as a means to drill students to solve problems. In word problem, students are demanded to be able to comprehend problems contexts that are given, make Math model from those problems, find ways to solve them and re-examine the results gotten. While in fact, it is shown that there are still a lot of students who find difficulties so that they make some errors in solving word problems. Related to the wills that appear to know the students’ behaviour and errors that are done by students while solving word problem by using Polya solving problem model. This study is focused to identify and classify errors that are done by students in solving word problems.. In addition, the reasons why the errors occur and hoe to solve them are going to be revealed here. This study uses qualitative descriptive approach. This research is done by students of fifth graders in SDN 1 Kebonsari Malang. The subjects of this study are chosen through the entrance test with errors variations and discussion results with teachers. There are eight students that are chosen who are divided into two students who have high ability, two students who have medium ability and four students who have low ability. Behaviour, types of errors and the reasons are gotten from the result of test and interview. The behaviour that is shown by the students of fifth graders in SDN 1 Kebonsari Malang are classified into four categories such as DTA-not proficient and DTA-proficient. Moreover, it is also found that there are other different reasons occur, but they are still related to the Pape behaviour problem solving, that is DTA-Limited Context + behaviour translation but without explanation, DTA Proficient + behaviour translation and DTA-Not Proficient + behavior translation. Based on the result of the study, it is suggested that teachers should know the errors that are often done by the students before the lesson begins to emphasize the teaching and learning process in those errors. Teachers are also able to give some practices, mainly in word problem to drill students’ experiment in solving them. Furthermore, the steps of solving the problems by using Polya model need to emphasize in terms of its usage so that it can practice students’ thinking process systematically. For the further research, if other researchers want to use this model to conduct further research so that they need to consider the application of this method in students and schools’ condition that are relatively different or other Math topics in the same subject.